2023
DOI: 10.1101/2023.02.22.529437
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single neurons in the human medial temporal lobe flexibly shift representations across spatial and memory tasks

Abstract: Investigations into how individual neurons encode behavioral variables of interest have revealed specific representations in single neurons, such as place and object cells, as well as a wide range of cells with conjunctive encodings or mixed selectivity. However, as most experiments examine neural activity within individual tasks, it is currently unclear if and how neural representations change across different task contexts. Within this discussion, the medial temporal lobe is particularly salient, as it is kn… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Several studies have found neural responses akin to the firing of place cells in rodents using similar tasks where subjects were instructed to navigate in a virtual arena and in which subjects have to learn to use their own location in conjunction with knowledge of a partially occluded arena in order to succeed at the task (Ekstrom et al, 2003;Miller et al, 2013). However, in other experiments in which subjects have to navigate to remote locations that are always in view, spatial target cells -cells that are significantly modulated by the target locations that subjects are navigating towards -were found instead of place cells, which were observed to a much lesser extent (Donoghue et al, 2023;Tsitsiklis et al, 2020). Collectively, a potential explanation of these findings is that the difference in encoding is related to the task demands, suggesting that hippocampal neurons are spatially-modulated, but the specific nature of this spatial coding (i.e., being directed at one's current location or on a remote / target location) can shift in a task-dependent manner, being driven by task demands that require or emphasize either self or remote locations in order to complete the task.…”
Section: Example 1: Representations Of Current / Self Vs Remote / Oth...mentioning
confidence: 91%
See 2 more Smart Citations
“…Several studies have found neural responses akin to the firing of place cells in rodents using similar tasks where subjects were instructed to navigate in a virtual arena and in which subjects have to learn to use their own location in conjunction with knowledge of a partially occluded arena in order to succeed at the task (Ekstrom et al, 2003;Miller et al, 2013). However, in other experiments in which subjects have to navigate to remote locations that are always in view, spatial target cells -cells that are significantly modulated by the target locations that subjects are navigating towards -were found instead of place cells, which were observed to a much lesser extent (Donoghue et al, 2023;Tsitsiklis et al, 2020). Collectively, a potential explanation of these findings is that the difference in encoding is related to the task demands, suggesting that hippocampal neurons are spatially-modulated, but the specific nature of this spatial coding (i.e., being directed at one's current location or on a remote / target location) can shift in a task-dependent manner, being driven by task demands that require or emphasize either self or remote locations in order to complete the task.…”
Section: Example 1: Representations Of Current / Self Vs Remote / Oth...mentioning
confidence: 91%
“…If, for example, a place cell is expected to only respond to space, after identification, this can be tested across tasks, comparing responses to various hypotheses regarding how a neuron might change activity if it is acting inline with a generalized cognitive map. In our recent work, we have started to address this question by combining a spatial navigation task with a working-memory task, finding neurons that had task-specific and taskindependent responses to relevant stimuli, as well as neurons that changed their representation across the two tasks -finding, for example, neurons that switch from representing stimuli in a working memory task, to representing serial position in a spatial navigation task -demonstrating a flexibility in the representations of hippocampal neurons (Donoghue et al, 2023).…”
Section: Example 4: Comparing Different Theoretical Framework Of Hipp...mentioning
confidence: 99%
See 1 more Smart Citation
“…Several contributions to the Special Issue of Hippocampus (2023) provide evidence that many primate hippocampal neurons respond to the location being viewed “out there,” not the place where the individual is located (Corrigan et al, 2023; Rolls, 2023b; Wirth, 2023; Zhu et al, 2023). Complementary evidence is also available for humans, in that in another paper in this Special Issue of Hippocampus, it was found that significant numbers of spatial view cells but not a significant number of place cells were found in the medial temporal lobe in a VR navigation task to the remembered location in a scene of a Treasure Chest (Donoghue et al, 2023). The spatial coordinates of these view cell representations are considered next.…”
Section: View Cell Spatial Coordinates: Allocentric Versus Facing Dir...mentioning
confidence: 95%
“…This is a commentary on issues important in understanding hippocampal function that are raised by papers in the Special Issue of Hippocampus (2023) entitled “Hippocampal system neurons encoding views in different species” (Alexander et al, 2023; Corrigan et al, 2023; Donoghue et al, 2023; LaChance & Taube, 2023; Lee et al, 2023; Quian Quiroga, 2023; Rolls, 2023b; Ryom et al, 2023; Wang et al, 2023; Wirth, 2023; Yang et al, 2023; Zhu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%